2014
DOI: 10.1016/j.msea.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon content on formation of bimodal microstructure and mechanical properties of low-carbon steels subjected to heavy-reduction single-pass hot/warm deformation

Abstract: A compression test simulating heavy-reduction single-pass rolling was conducted to investigate the microstructural evolution based on the formation of a bimodal structure and the mechanical properties of 0.01% and 0.1% carbon steels and niobium steel. When thermomechanical processing was conducted near and above the critical transformation temperature (A c3 ), microstructures of all steels were significantly refined and consisted of equiaxed grains without elongated grains. Nevertheless, these microstructures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Elongated structures were mostly observed and the fraction of elongated ferrites decreased with increasing heating temperature from 700 to 800 The initial coarse structure with an average ferrite grain size of about 41 µm consisting of coarse ferrite and pearlite structures was transformed into fine ferrite and finely dispersed pearlite or cementite structures, and the ferrite grains were considerably refined after the single-pass heavy-reduction controlled rolling process near or above the critical transformation temperature (A c3 ). This result shows good agreement with our previous studies using 0.01, 0.1, and 0.2% carbon steels as well as a niobium steel subjected to the PSC test near or above A c3 , simulating heavy-reduction single-pass controlled rolling [42,43]. Furthermore, it has been well known that grain size was significantly reduced by the strain-induced transformation (γ→α) in various steels during the thermomechanical treatment near A c3 or A r3 [46][47][48][49].…”
Section: Microstructural Evolution Of 02% Carbon Steel With Differensupporting
confidence: 91%
See 2 more Smart Citations
“…Elongated structures were mostly observed and the fraction of elongated ferrites decreased with increasing heating temperature from 700 to 800 The initial coarse structure with an average ferrite grain size of about 41 µm consisting of coarse ferrite and pearlite structures was transformed into fine ferrite and finely dispersed pearlite or cementite structures, and the ferrite grains were considerably refined after the single-pass heavy-reduction controlled rolling process near or above the critical transformation temperature (A c3 ). This result shows good agreement with our previous studies using 0.01, 0.1, and 0.2% carbon steels as well as a niobium steel subjected to the PSC test near or above A c3 , simulating heavy-reduction single-pass controlled rolling [42,43]. Furthermore, it has been well known that grain size was significantly reduced by the strain-induced transformation (γ→α) in various steels during the thermomechanical treatment near A c3 or A r3 [46][47][48][49].…”
Section: Microstructural Evolution Of 02% Carbon Steel With Differensupporting
confidence: 91%
“…There were many dislocations, which were introduced inside the microstructure through the controlled rolling process. This process formed fine ferrites, and fine pearlite or cementite particles from the coarse pearlite lamellae as well as substructures such as subgrains in the ferrites instead of generating new grains with HAGBs because of the high stacking fault energy of ferrite [42,43,57]. This led to not only an increase in the fraction of Fig.…”
Section: Microstructural Evolution Of 02% Carbon Steel With Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…A ferrite having a high stacking fault energy (SFE) caused an increase in the fraction of LAGBs during warm forming around the transformation temperature ( A c1 ), leading to a decrease in ductility despite an increase in strength . Saray et al reported that the heavily elongated grain morphology in IF steel resulted in low formability owing to the increased tendency for cracking to occur through elongated grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…We have proposed a new concept for manufacturing bimodal steel sheets having micron‐size grains (1–5 μm) distributed in a submicron‐size matrix (<1 μm) in a low‐carbon steel with an outstanding balance between strength and elongation by inducing a phase transformation (γ→α) after SPD slightly above the critical transformation temperature ( A c3 ) (Figure ). In our previous investigations, the formation of a bimodal structure with coexisting submicron‐size (<1 μm) and micron‐size grains (1–4 μm) in 0.2% carbon steel and its excellent mechanical properties were revealed by conducting plane‐strain compression (PSC) tests and single‐pass heavy‐reduction rolling. In our hot rolling test with one‐pass reduction of 75%, using 0.2% carbon steel with different heating temperatures, it was demonstrated that the proposed ‐rolling process is capable of producing a bimodal steel strip with an excellent balance between cold formability and strength.…”
Section: Introductionmentioning
confidence: 99%